La première personne du singulier - Dinah Ribard (Les Dossiers du GRIHL)
First person singular. In Michel de Certeau's work, literature is not the name for a corpus, nor for several corpuses. The word, basically, is not used to distinguish some writings from others. Literature is what is written; it is the totality formed by everything that is written. Something has happened, something has appeared, something has disappeared, literature is being written; it is accumulating. History is part of it: history creates a difference within what Certeau often calls "a literature", a literature about the past. Moreover, for him, the moment when what is written becomes history – the reciprocal foundation of the past as past and of the present as different from it - is expressed by resorting to the first person singular. This article proposes some remarks on this history operator, « I » ‒ je ‒, in Certeau's reflection and in his analyses of writings written in the first person, for which he makes use of the distinction between "constative" formality (i. e., the description of ideas and things) and "performative" formality which allows to understand the "text".